Peran Kader Posyandu Dalam Meningkatnya Cakupan Kunjungan Balita Di Wilayah Kerja Desa Sukaluyu Karawang - Betteria Purba Purba; Titin Eka Sugiantini (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Background according to the District Health Office. Karawang in 2020 The achievement of toddler health services is 77.2%. While the coverage per puskesmas tirta jaya is 21.68, puskesmas pakisjaya is 26.98 while puskesmas Teluk Jambe is 18.878%.Research purposes: It is known that the role of posyandu cadres in increasing the coverage of toddler visits in the working area of Sukaluyu Karawang Village in 2023.Research methods: Using analytics with a cross sectional approach. The population of this research is posyandu cadres, totaling 162. The research sample is 62 respondents.analis bivariate use testwho squares.Research result: The results of the chi square test showed a significant value of p = 0.000, which meant that there was a relationship between the role of Posyandu toddler cadres and toddler visits in the working area of Sukaluyu Village Karawang district in 2023.Conclusions and recommendations:Â In conclusion, there is a relationship between the role of Posyandu cadres for toddlers and toddler visits in the working area of Sukaluyu Village Karawang district in 2023. Recommended in this research for educational institutions, for research sites, for respondents and for further researchers.